670nm light treatment following retinal injury modulates Müller cell gliosis: Evidence from in vivo and in vitro stress models. (April 2018) - Lu, Yen-Zhen; Fernando, Nilisha; Natoli, Riccardo; Madigan, Michele; Valter, Krisztina
Abstract: Photobiomodulation (PBM) with 670 nm light has been shown to accelerate wound healing in soft tissue injuries, and also to protect neuronal tissues. However, little data exist on its effects on the non-neuronal components of the retina, such as Müller cells (MCs), which are the principal macroglia of the retina that play a role in maintaining retinal homeostasis. The aim of this study was to explore the effects of 670 nm light on activated MCs using in vivo and in vitro stress models. Adult Sprague-Dawley rats were exposed to photo-oxidative damage (PD) for 24 h and treated with 670 nm light at 0, 3 and 14 days after PD. Tissue was collected at 30 days post-PD for analysis. Using the in vitro scratch model with a human MC line (MIO-M1), area coverage and cellular stress were analysed following treatment with 670 nm light. We showed that early treatment with 670 nm light after PD reduced MC activation, lowering the retinal expression of GFAP and FGF-2. 670 nm light treatment mitigated the production of MC-related pro-inflammatory cytokines (including IL-1β), and reduced microglia/macrophage (MG/MΦ) recruitment into the outer retina following PD. This subsequently decreased photoreceptor loss, slowing the progression of retinal degeneration. In vitro, we showed that 670 nm light directly modulated MC activation, reducing rates of area coverage by suppressing cellular proliferation and spreading. This study indicates that 670 nm light treatment post-injury may have therapeutic benefit when administered shortly after retinal damage, and could be useful for retinal degenerations where MC gliosis is a feature of disease progression. Highlights: Using in vivo and in vitro models, we showed that photobiomodulation with 670 nm light: Reduced glial scar formation in photo-oxidative stress model or retinal degeneration. Reduced Müller cell-mediated recruitment of microglia and macrophages. Can reduce the extent of reactive and proliferative gliosis of Müller cells both in vivo and in vitro . Decrease cell migration and proliferation in the human Müller cell line. We showed that early therapeutic window with 670 nm light led to the most protection from progressive retinal degeneration.